Student Academic Success Factors in Selected Nursing Collages in Saudi Arabia - Mohmmed Amer Alsoqae, Aysha; Belal, Safia (International Journal of Innovative Research in Medical Science, 2024)
Background: Academic achievement is a crucial requirement for students to graduate, but its definition is complex and multifaceted. Academic aspects play a crucial role in nursing education, affecting students' success and development. Aim: The present study was conducted with aim to determine the student's perception about academic success also to assess the factors that affect students' academic success among nursing students is Saudi Arabia. Method: This research adopts a descriptive cross-sectional design to investigate factors influencing academic success among nursing students in selected Saudi Arabian colleges. The study is conducted at King Faisal University and Najran University, with a sample size of 400 nursing students chosen through purposive convenient sampling. Data is collected via a structured questionnaire covering socio-demographic details, learning styles, and perceptions of academic success. Findings: Results reveal a majority of nursing students who are predominantly female, aged 18-23, hailing from urban areas, and single. Most students willingly chose nursing, appreciate their specialty, and exhibit positive perceptions of academic success. Learning style preferences indicate a preference for cooperative learning, discovery learning, and self-education. Significant associations are identified between university choice and various demographic and academic factors. Perceptions about personal, psychological, college/university-related, home-related, and teacher-related factors are generally positive. Correlations between university choice and these perceptions are established. Conclusion: In conclusion, this study provides valuable insights into the intricate factors influencing academic success among nursing students in Saudi Arabian colleges. Emphasizing the importance of university-specific dynamics in shaping students' experiences and perceptions, the findings contribute crucial information for tailoring educational strategies and interventions. Keywords: Academic Success Factors, Nursing, Saudi Arabia, Student.